Ex 9.5, 4 - Simplify (i) (a^2 - b^2)^2 (ii) (2x + 5)^2 - (2x - 5)^2

 

 

 

  1. Chapter 9 Class 8 Algebraic Expressions and Identities
  2. Serial order wise

Transcript

Ex 9.5, 4 Simplify. (i) (π‘Ž^2βˆ’π‘^2 )^2 (π‘Ž^2βˆ’π‘^2 )^2 (π‘₯βˆ’π‘¦)^2=π‘₯^2+𝑦^2βˆ’2π‘₯𝑦 Putting π‘₯ = π‘Ž^2 & 𝑦 = 𝑏^2 = (π‘Ž^2 )^2+(𝑏^2 )^2βˆ’2(π‘Ž^2 )(𝑏^2 ) = π‘Ž^(2 Γ— 2)+𝑏^(2 Γ— 2)βˆ’2π‘Ž^2 𝑏^2 = 𝒂^πŸ’+𝒃^πŸ’βˆ’πŸπ’‚^𝟐 𝒃^𝟐

About the Author

Davneet Singh's photo - Teacher, Engineer, Marketer
Davneet Singh
Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 10 years. He provides courses for Maths and Science at Teachoo.